Penguatan Pembelajaran Praktik Melalui Pelatihan Penggunaan Trainer Mikrokontroler di SMK Negeri 2 Gowa - Riana T Mangesa; Elfira Makmur; Wahyudi; Muhammad Iswal Burhan; Muhammad Yahya (Vokatek: Jurnal Pengabdian Masyarakat, 2023)
The use of microcontrollers as a practical learning tool in Vocational High Schools (SMK) plays an important role in developing students' technical skills. This research aims to strengthen practical learning at SMK Negeri 2 Gowa through training in the use of microcontroller trainers. The research method used was a qualitative approach involving instructors and students as research subjects. The training was conducted with a focus on mastering the basic concepts of using microcontrollers, developing programming skills, and practical applications in various projects. The evaluation results showed a significant improvement in students' understanding of microcontroller concepts and their ability to apply the knowledge in practical situations. In addition, the instructors also provided positive feedback regarding the effectiveness of the microcontroller trainer as a learning tool. Strengthening practical learning through training in the use of microcontroller trainers at SMK Negeri 2 Gowa contributed positively to improving the quality of technical learning at this school. The results of this study are expected to be a reference for other SMKs that want to improve the effectiveness